Creative and Innovative Learning Through Environmental Empowerment, Gajah Wong Clean River Program - Palupi, Retno Endah (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
Kali Gajah Wong is a river located in Kampung Giwangan, Yogyakarta, which was previously known as a slum area. Through a community empowerment program initiated by the Mrican Youth community, Kali Gajah Wong has transformed into a tourist village. This article discusses the application of creative and innovative learning in the environmental empowerment of Kampung Kali Gajah Wong. The research employs a literature study method by examining research articles related to the community empowerment of Kali Gajah Wong. The results show that creative and innovative learning has been implemented through various training programs for local residents, such as waste management, processed fish products, and so on. These activities aim to enhance the skills and productivity of the residents while creating distinctive village products as branding for the Kali Gajah Wong tourist village. It can be concluded that creative and innovative learning is highly applicable in real community empowerment through direct observation of its benefits.